Endovascular Closure of Secundum Atrial Septal Defects with Complex Anatomy - Ditkivskyy, Igor O.; Petrov, Maksym S.; Voloshyn, Denys L.; Yashchuk, Nataliia S.; Lazoryshynets, Vasyl V. (Ukrainian Journal of Cardiovascular Surgery, 2023)
According to European guidelines, endovascular closure is the method of choice for defects with favorable anatomy. However, there are no clear criteria for determining favorable anatomy and this issue requires additional investigation. According to literature data, only 24.2% of secundum atrial septal defects (ASDII) have a central location, others have complicated anatomy. The aim. To analyze the experience of endovascular closure of ASDII with complex anatomy. Materials. In the period from 2003 to 2021, 1732 transesophageal echocardiographies and intracardiac echocardiographieswereperformedinpatientswithASDIIinitiallydiagnosedaccordingtotransthoracicechocardiography, and only 1408 (91.8%) were selected for endovascular closure. Mean age was 19.9±18 years, mean weight was 45±26.68 kg. Methods. The standard closure technique was primarily used in 100% of cases, and only when it was ineffective, we used modified techniques. Results. Modified techniques were used in 478 (33.9%) of 1408 patients and were effective in 460 (96.2%) patients with the complex anatomy. Based on previous statement, 460 (32.6%) of 1408 patients (one third of all) had modified techniques utilized and avoided open surgery. In 18 (1.3%) cases, it was impossible to close the defect. The overall technical success of transcatheter closure was 98.7% (1390 patients). Nineteen (1.3%) patients with poor visualization of inferior rim on transesophageal echocardiography had intracardiac echocardiography; in two of them inferior rim was present, others had open surgery. The rate of complications in immediate periprocedural period was 1.9% (27 patients). One death was recorded in the period of introduction of percutaneous interventions in our institution. Mean follow-up period was 5.41±3.28 years. In the follow-up period two complications were observed: 1 case of erosion, 17 (1.9%) cases of new-onset atrial fibrillation. Conclusion. The majority (90.6%) of ASDII can be closed percutaneously. Modified techniques improve the efficacy of the procedure enabling to close 32.6% of the defects. Safe procedure for the defects with complex anatomy is possible only with surgical and arrhythmological services back-up.